Determination of sildenafil, vardenafil and tadalafil in dietary supplements sold in the Yemeni market - Al-Tahami, Khaled (World Wide Journals, 2014)
There have been a number of reports of dietary supplements contaminated with illegal adulterants that threaten consumers health for their adverse pharmacological effects worldwide. In this study, our main aim was to investigate different dietary supplements of different forms present in the Yemeni market for the presence of sildenafil, vardenafil and tadalafil. An HPLC method was adopted for this study to investigate for their presence simultaneously. The mobile phase consisted of acetonitrile and aqueous solution containing ammonium acetate and formic acid using the gradient elution system at a detection wavelength of 292 nm. All of the samples were found to contain at least one of the investigated medicines. The confirmatory studies were performed by thin layer chromatography. Results obtained confirmed the presence of the investigated drugs in the dietary supplements tested.